Inhibition of nitric oxide synthesis promotes increased mortality despite the reduction of parasitemia in Plasmodium berghei-infected mice - Barbosa, Aline da Silva (2021)
Nitric oxide (NO) is an important mediator molecule in inflammatory processes, but its role in the pathophysiology of malaria is still uncertain. To investigate the NO synthesis inhibition on the oxidative changes induced by Plasmodium berghei infection in mice, malaria was induced in 150 animals, of which 75 animals were treated with the NO inhibitor L-NAME; the remaining animals were sham controls. All animals underwent euthanasia 1, 5, 10, 15, or 20 days after infection for the collection of lungs, brain, and blood. Parasitemia was determined, and the survival of the animals was evaluated. Tissue samples were assayed for nitrites and nitrates (NN), thiobarbituric acid reactive substances (TBARS), and total Trolox equivalent antioxidant capacity (TEAC). A histopathological study was performed. Mortality rates in the L-NAME group were always higher than those in the controls. In the brain, NN was lower in the L-NAME group. Parasitemia and its progression rate were greater in the control group. By the 5th day of infection, mice treated with L-NAME showed cerebral edema and interstitial pneumonia of greater intensity than controls. In conclusion, the anti-inflammatory and hemodynamic effects of NO surpass its pro-oxidant role in murine malaria.